Regulation of T cell function by protein S-acylation - West, Savannah J.; Boehning, Darren; Akimzhanov, Askar M. (Frontiers in Physiology, 2022)
S-acylation, the reversible lipidation of free cysteine residues with long-chain fatty acids, is a highly dynamic post-translational protein modification that has recently emerged as an important regulator of the T cell function. The reversible nature of S-acylation sets this modification apart from other forms of protein lipidation and allows it to play a unique role in intracellular signal transduction. In recent years, a significant number of T cell proteins, including receptors, enzymes, ion channels, and adaptor proteins, were identified as S-acylated. It has been shown that S-acylation critically contributes to their function by regulating protein localization, stability and protein-protein interactions. Furthermore, it has been demonstrated that zDHHC protein acyltransferases, the family of enzymes mediating this modification, also play a prominent role in T cell activation and differentiation. In this review, we aim to highlight the diversity of proteins undergoing S-acylation in T cells, elucidate the mechanisms by which reversible lipidation can impact protein function, and introduce protein acyltransferases as a novel class of regulatory T cell proteins.